Does the interval of screening endoscopy affect survival in gastric cancer patients?: A cross-sectional study. Issue 49 (December 2016) - Kim, Jieun; Kim, Su Mi; Ha, Man Ho; Seo, Jeong Eun; Choi, Min-Gew; Lee, Jun Ho; Sohn, Tae Sung; Kim, Sung; Jung, Sin-Ho; Bae, Jae Moon
Abstract : Abstract: Gastric cancer remains the second most common cancer in Korea; however, its mortality has decreased due to earlier diagnosis. In Korea, screening endoscopy has been performed nationwide since 1999. The aim of this study was to elucidate the benefit of screening endoscopy on actual survival in gastric cancer patients and to determine the optimal interval of screening endoscopy. We analyzed 1651 patients diagnosed with gastric adenocarcinoma who underwent surgical treatment between June 2008 and December 2014. Patients were divided into 4 groups according to the interval of screening endoscopy prior to their gastric cancer diagnosis. (Group I = within 1 year, Group II = >1 but <2 years, Group III = more than 2 years, Group IV = no prior endoscopic examination). Patient demographics, clinicopathologic characteristics, and postoperative surgical outcomes including overall survival were compared. The 5-year gastric cancer-specific survival rates of groups I and II were significantly higher than groups III and IV (90.9% vs 85.4%, P = 0.002, respectively). Multivariate analysis showed that screening interval was an independent factor for the diagnosis of advanced gastric cancer. The risk of advanced gastric cancer decreased in group I (odds ratio: 0.515, 95% confidence interval [CI] 0.369–0.719; P < 0.001) and group II (odds ratio: 0.678, 95% CI 0.517–0.889, P = 0.005). Screening endoscopy was helpful in increasing the survival of gastric cancer patients. A 2-year endoscopic screening interval is suitable to detect early-stage gastric cancer.